Antinociceptive Activity of Essential Oils from Wild Growing and Micropropagated Plants of Renealmia alpinia (Rottb.) Maas (2019)
ABSTRACT: Renealmia alpinia is a medicinal plant that has been cultivated and used for the treatment of headaches, abdominal pain, as a febrifuge and to treat snake bites in southeast Colombia and in the Caribbean islands. Moreover, its edible fruits are commonly used as spice in Mexico. The R. alpinia leave-extracts have shown enzymatic inhibition of Bothrops atrox and Bothrops asper snake poison. The extracts also showed effects as a peripheral analgesic agent. This report investigates the analgesic activity of the essential oils obtained by hydrodistillation from wild and in vitro propagation samples of R. alpinia as well as the chemical profile using GC-MS. The essential oils isolated from R. alpinia evaluated on concentrations of 50, 75 and 100 mg/kg showed significant antinociceptive effects in the test of acetic-acid-induced abdominal writhing, compared to the control animals. The essential oil of the wild flora leaves showed the highest percentage of pain inhibition by 200 mg/kg, concluding that the essential oil of R. alpinia presents antinociceptive activity in an in vivo model. These results help us to understand the traditional use of R. alpinia to treat pain and make it a potential source for the development of phytopharmaceutics.